2019
DOI: 10.1002/bsl.2420
|View full text |Cite
|
Sign up to set email alerts
|

Technological advances in the assessment of impulse control in offenders: A systematic review

Abstract: Deficits in impulse control have been linked to criminal offending, risk of recidivism, and other maladaptive behaviours relevant to the criminal justice system (e.g. substance use). Impulse control can be conceptualized as encompassing the broad domains of response inhibition and impulsive/risky decision‐making. Advancements in technology have led to the development of computerized behavioural measures to assess performance in these domains, such as go/no‐go and delay discounting tasks. Despite a relatively l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(89 reference statements)
2
10
0
Order By: Relevance
“…Consistent with the considerable literature indicating that antisocial individuals generally show significantly greater TDI than comparison individuals (for a review, see Vedelago et al 2019) and one of the previous results with participants with CD [ (White et al 2014) although see (Fanti et al 2016)], the participants with CD in the current study showed significantly greater TDI than typically developing participants. It is possible that the inconsistency of the current results with those of Fanti et al (2016) reflects the younger average of participants in that study (10.94 years relative to 16.45 years here); that is, there is a developmental component to the emergence of the TDI impairment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the considerable literature indicating that antisocial individuals generally show significantly greater TDI than comparison individuals (for a review, see Vedelago et al 2019) and one of the previous results with participants with CD [ (White et al 2014) although see (Fanti et al 2016)], the participants with CD in the current study showed significantly greater TDI than typically developing participants. It is possible that the inconsistency of the current results with those of Fanti et al (2016) reflects the younger average of participants in that study (10.94 years relative to 16.45 years here); that is, there is a developmental component to the emergence of the TDI impairment.…”
Section: Discussionsupporting
confidence: 90%
“…A considerable literature indicates that antisocial adults show significantly greater TDI than comparison individuals (for a review, see Vedelago et al 2019). However, surprisingly, few studies have examined TDI in adolescents with conduct disorder (CD) (White et al 2014;Fanti et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…From a forensic point of view, EF is of great interest because it could negatively interfere with one’s ability to interpret interpersonal cues and hence could lead to act impulsively and aggressively, or in any other antisocial way (Valliant et al., 2003). Indeed, research suggests a causal relationship between deficits in EF and misconduct (Ogilvie et al., 2011, Vedelago et al., 2019). Reversely, individuals with an ‘intact’ EF are more likely to self-regulate and inhibit disturbing emotions, hence guarding against offending (Adjorlolo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The poor conceptualization of impulsivity constructs in studies focusing on forensic populations is problematic because such information is increasingly relevant for the criminal justice system, especially for the treatment of forensic patients (Bootsman, 2019), and for risk assessment (Cheng et al, 2019; & Raine, 2006). Questionnaires -mostly measuring trait impulsivity -are often used for forensic assessment, but recent research suggests that experimental psychology tasks may complement existing assessment tools, because they are less sensitive to socially desirable answers, more versatile, and suitable for individuals across the literacy spectrum (Vedelago et al, 2019). Impulsivity measured with self-reported questionnaires or experimental psychological tasks may reflect different behavioral tendencies (Cyders, 2015).…”
mentioning
confidence: 99%
“…Recent reviews and meta-analyses indicate that offenders experience more difficulties on RRI tasks compared to controls (Vedelago et al, 2019) and that RRI is implicated in many psychopathologies and maladaptive behaviors, including attention-deficit hyperactivity disorder (Wright et al, 2014), aggression (Puiu et al, 2018), and antisocial behavior in general (Ogilvie et al, 2011). Studies assessing RRI in offending populations generally use non-emotional stimuli (Vedelago et al, 2019), whereas RRI problems mainly manifest in emotionally demanding or stressful situations, and reviews therefore stress the importance of contingencies such as emotions and stress in assessing response inhibition (Eben et al, 2020;Tittle et al, 2003).…”
mentioning
confidence: 99%